EPID-08. EFFECT OF HEALTH DISPARITIES ON OVERALL SURVIVAL OF PATIENTS WITH GLIOBLASTOMA. (5th November 2018) - Mandel, Jacob; Youssef, Michael; Nam, Jooyeon; Patel, Akash; Liu, Diane; Wu, Jimin; Armstrong, Georgina; Bondy, Melissa; de Groot, John
Abstract: BACKGROUND: Glioblastoma (GB) is the most common primary malignant brain tumor in adults. It remains uncertain the potential effects of health disparities in this patient population. METHODS: We conducted a retrospective chart review of newly diagnosed GB patients from 2000–2015 at a free standing dedicated cancer center (MD Anderson Cancer Center - MDACC) and a safety net county hospital (Ben Taub General Hospital - BT) located in Houston, Texas. We obtained demographics, insurance status, clinical variables, extent of resection, treatment, and other known prognostic variables (Karnofsky Score – KPS) to evaluate their role on overall GB survival (OS). RESULTS: We identified 1, 073 GB patients consisting of 177 from BT and 896 from MDACC. We found significant differences by ethnicity, primary language, insurance status, marital status, KPS at diagnosis, extent of resection, and percentage of patients receiving standard of care (SOC) consisting of concurrent chemoradiation followed by adjuvant temozolomide between the two centers. OS was 1.64 years for MDACC patients and 1.24 years for BT patients (p<0.0176). Of the 177 BT patients, 40 (23%) had KPS KPS <70 at diagnosis, compared to 6 (0.01%) of the 896 MDACC patients. Only 81 (45.8%) of BT patients received SOC compared to 577 (64%) of MDACC patients (p<0.0001). However, there was no significant difference in OS for patients who received SOC, 1.84 years for MDACC patients and 1.99 years for BT patients (p<0.4787). Of the 96 BT patients who did not receive SOC, 29 (30%) had a KPS less than 70 at time of diagnosis and 77 (80%) did not have insurance. CONCLUSIONS: GB patients treated at a safety net county hospital had similar OS compared to a free standing comprehensive cancer center when receiving SOC. County hospital patients had poorer KPS at diagnosis and were often lacking health insurance potentially affecting their ability to receive SOC.